Biological Impact of Gold Nanoparticle on Estradaiol and Testosterone Levels in Sera of Human Males - Abdulsattar, Sura A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: There is a little information on the potential nanoparticle risk to human health, particularly on the sex hormones.Objectives: the present study aims to investigate the impact of gold nanoparticles potential toxicity on the levels of sex hormones testosterone (T) and estradiol (E2) in sera of human malesPatients and methods: a total of 25 healthy men volunteers aged (20-45) years participated. Four types of gold nanoparticles were used to study their impact on estradiol and testosterone levels.Results: The results indicated inhibiting effect of gold nanoparticles on E2 level and activating effect on T level .The low impact of T/E2 by gold nanoparticles was executed at 20μl serum.Conclusion: different types of gold nanoparticles have an impact on sex hormone binding to their receptors and thus effect on its level in the blood, hence affects the biological processes that are dependant on hormone concentration.